The Influence of the Ionic Core on Structural and Thermodynamic Properties of Dense Plasmas - Tomiris Ismagambetova; Mukhit Muratov; Maratbek Gabdullin (Plasma)
In this paper, a new ion–ion screened potential was numerically calculated, which takes into account the ion core effect, i.e., the influence of strongly bound electrons. The pseudopotential model describing the shielding of ion cores and the screening using the density response function in the long wavelength approximation were used. To study the influence of this ion core effect on dense plasma’s structural and thermodynamic properties, the integral Ornstein–Zernike equation was solved in the hypernetted chain approximation. Our results show that the ion core has a significant impact on ionic radial distribution functions and thermodynamic properties when compared to the results obtained for the Yukawa potential, which does not take the ion core into account. Increasing the steepness of the core edge or decreasing the depth of the minimum leads to more pronounced screening due to bound electrons.